Anti-seizure effects of Datura stramonium: Impact on neurobehavior, antioxidant enzymes, and inflammatory markers in the hippocampus and amygdala of adult female Wistar rats using an isoniazid-induced epileptic model - Nto Johnson Nto; Somterimam Dogara Paul; Christian Mba; Godson Emeka Anyanwu; Uloaku Akubueze Nto-Ezimah; Emmanuel Obeagu; Chioma Ekenna-Ohanenye (Journal of Krishna Institute of Medical Sciences University)
Background: Epilepsy, marked by recurrent seizures and neurochemical imbalances, remains a treatment challenge, particularly in resource-limited settings. Datura Stramonium (DS), a plant rich in tropane alkaloids like atropine, scopolamine, and hyoscyamine, has demonstrated potential pharmacological effects on the nervous system. However, its antiepileptic and neuroprotective properties are not well-studied. Aim and Objectives: This study assessed the anti- seizure potential of DS and its effects on neurobehavioral parameters, antioxidant enzyme activity, and inflammatory markers in an isoniazid-induced epileptic model in adult female wistar rats. Material and Methods: DS extract was prepared using a standard extraction protocol. Group 1 was fed with water and standard feed only; group 2 was induced with 300 mg/kg of isoniazid only; group 3 was given low dose DS extract (60 mg/kg) only; group 4 was given high dose DS extract (120 mg/kg) only; group 5 (standard drug) was pre-treated with carbamazepine (200 mg/kg) and seizure was induced with isoniazid (300 mg/kg); groups 6 and 7 were pre-treated with low (60 mg/kg) and high (120 mg/kg) dose DS extract respectively, and induced with isoniazid (300 mg/kg).Seizure traits were monitored while the threshold and latency were scored for anti-epileptic assessment. Oxidative stress levels were assessed using the superoxide dismutase, catalase, and malondialdehyde biomarkers, and TNF-α levels were also assessed for pro-inflammatory reactions. The histology of the hippocampus and amygdala, stained with haematoxylin and eosin, was studied. Results: The results revealed that low-dose DS (60 mg/kg) significantly reduced seizure latency, increased the seizure threshold, showed mild anxiolytic and improved cognitive abilities in behaviour, and also exhibited neuroprotective effects on the hippocampal and amygdala cytoarchitecture against isoniazid-induced epilepsy. DS extract also showed significant anti-inflammatory and antioxidant abilities. Conclusion: These findings suggest that DS possesses neuroprotective, anti-oxidative, and anti-inflammatory effects, as well as being a potent anti-epileptic agent.